The Role of Perceived Social Support on Academic Stress (Prithvi Academic Journal, 2020)
Academic stress has many negative effects on the students, and support from different levels can prevent this. This cross-sectional survey study among 322 students of class 8 and 10 from 3 public schools in Pokhara, Nepal was conducted to identify the role of perceived social support (PSS) from different levels (family, friends, and others) on academic-stress of students. The schools and participants were selected through a multistage cluster sampling technique. To collect the data self-administered questionnaires were distributed to the participants in their respective classrooms by one of the researchers. The data were analyzed in SPSS 20 with descriptive and inferential statistics (chi-square test and odds ratio at 95% confidence interval) at